Enhanced electrochemical performance by size-dependent SEI layer reactivation of NiCo2O4 anodes for lithium ion batteries. (20th February 2019) - Ren, Qing-Qing; Yu, Fu-Da; Zhang, Si-Wen; Yin, Bo-Si; Wang, Zhen-Bo; Ke, Ke
Abstract: Under over-increasing demand of advanced lithium-ion batteries (LIBs) for long-range electric vehicles (EVs), high-capacity transition metal oxide (TMO) negative electrodes for LIBs are thought as potential substitutes of traditional graphite anodes. A major barrier for TMO anodes is volumetric expansion during lithiation processes, leading to active material pulverization and falling off current collectors, which seriously deteriorates capacity retention. Herein, apart from conventional mechanical degradation, another capacity fading mechanism is revealed. Furthermore, the understanding is supported by an interesting cycling property. Firstly, NiCo2 O4 with designed morphologies of nanoplates and microspheres are studied for the initial (de)lithiation and prolonged cycles. The morphology changes indicate solid electrolyte interphase (SEI) layer accumulating on the surface of electrodes and impeding the contact and reactions between lithium and active materials with a result of severe capacity loss. It can be understood as SEI layer insulating NiCo2 O4, and if SEI film appropriately changes, high capacities can recovery. This conjecture is confirmed by following research of NiCo2 O4 nanoparticles with amazing cycling performance prepared by a facile water-bath method. As LIB anodes, NiCo2 O4 nanoparticles exhibit capacities of 1144 mAh g −1 at the initial discharging, 230 mAh g −1 at the 100 th cycle and 661 mAh g −1 at the 500 th cycle. The corresponding coulombic efficiency is of 73.1%, 98.4% and 99.5%, respectively. By TEM characterization in combination with electrochemical analysis, size-dependent SEI layer reactivation (from thick and unstable to thin and stable) is a key role on the dramatic capacity recovery.